Improvement in Activity of Daily Living and Fatigue in Multiple Sclerosis Patients: the Impact of Nutrition Education - Rashvand; Abtahi; Moshtagh Eshgh; Farvid; Pouraram (Kashan University of Medical Sciences, 2016)
Background Fatigue is one of the most common complications of Multiple Sclerosis (MS). However, a few studies are available on the effect of nutrition education on fatigue and Activities of Daily Living (ADL) in patients with MS. Objectives This study aimed to assess the effect of nutrition education on fatigue and ability to perform ADL in patients with MS. Methods This quasi-experimental one group, pretest and posttest study was performed on 40 patients with MS, who were conveniently recruited among patients, registered at the Iranian MS Society. Data were collected through a demographic questionnaire, the Fatigue Severity Scale (FSS), a standard ADL scale, and a 24-hour food recall for two days. The instruments were completed at the start and two months after the intervention. Descriptive statistics and paired t test were used to analyze the data. Results Sixty percent of the patients had severe fatigue before the intervention while, 90% of them reported mild fatigue after the intervention. The mean posttest ADL was increased by 12.45 units after the intervention when compared with the pretest value (P<0.001). Moreover, the daily intake of vitamin D and E, calcium and omega3 were lower than 75% of the Dietary Reference Intake (DRI) in most of the patients. Conclusions The present study showed the beneficial effects of nutritional training on fatigue and ADL in patients with MS. Therefore, nurses and dietitians should regularly assess the patients' dietary pattern and train them and their families about appropriate diet.